Application of information technology within a field hospital deployment following the January 2010 Haiti earthquake disaster - Levy, Gad (BMJ Group, 2010)
Following the January 2010 earthquake in Haiti, the Israel Defense Force Medical Corps dispatched a field hospital unit. A specially tailored information technology solution was deployed within the hospital. The solution included a hospital administration system as well as a complete electronic medical record. A light-weight picture archiving and communication system was also deployed. During 10 days of operation, the system registered 1111 patients. The network and system up times were more than 99.9%. Patient movements within the hospital were noted, and an online command dashboard screen was generated. Patient care was delivered using the electronic medical record. Digital radiographs were acquired and transmitted to stations throughout the hospital. The system helped to introduce order in an otherwise chaotic situation and enabled adequate utilization of scarce medical resources by continually gathering information, analyzing it, and presenting it to the decision-making command level. The establishment of electronic medical records promoted the adequacy of medical treatment and facilitated continuity of care. This experience in Haiti supports the feasibility of deploying information technologies within a field hospital operation. Disaster response teams and agencies are encouraged to consider the use of information technology as part of their contingency plans.